Museo de Xul Solar - Beitia, Pablo Tomás; Iglesia, Rafael E. J. (1997)
Acerca del Museo de Xul Solar.
Keywords: EDIFICIOS CULTURALES; MUSEOS; MUSEOS DE ARTE; BUENOS AIRES; REFUNCIONALIZACION ARQUITECTONICA; ARGENTINA